A River's Gifts : The Mighty Elwha River Reborn - Newman, Patricia, 1958-; Donovan, Natasha (Minneapolis : Millbrook Press, 2023)
"There's more to a river than meets the eye. The story of the Elwha River in Washington State is one of both environmental harm and restoration involving advocacy, persistence, cooperation, and hope"--
Includes bibliographical references.
Keywords: Restoration ecology -- Juvenile literature. -- Washington (State); Wildlife management -- Juvenile literature. -- Washington (State); Wildlife habitat improvement -- Juvenile literature. -- Washington (State); Natural history -- Juvenile literature. -- Washington (State); Restoration ecology -- Washington (State); Wildlife management -- Washington (State); Animal ecology -- Washington (State); Natural history -- Washington (State); Picture books